Comparative analysis of germ cells and DNA of the genus Amblyomma: adding new data on Amblyomma maculatum and Amblyomma ovale species (Acari: Ixodidae) - Rivera-Páez, Fredy Arvey [UNESP]; Sampieri, Bruno Rodrigues; Labruna, Marcelo Bahia; da Silva Matos, Renata [UNESP]; Martins, Thiago Fernandes; Camargo-Mathias, Maria Izabel [UNESP] (Springer Nature, 2017)
Among tick species, members of the subfamily Amblyomminae have received special attention, since they serve as vectors for pathogens such as Rickettsia spp. and display cryptic species complexes that make their taxonomical classification challenging. Amblyomma ovale, Amblyomma maculatum, and other species of the genus Amblyomma have shown a long history of taxonomic controversies. Spermiotaxonomy has proved to be a valuable tool in the solution of systematic conflicts in Metazoa that can aid molecular and external morphological analyses in ticks and, overall, provide more robust analyses and results. With this in mind, this study included histological analyses of the reproductive system of the species A. ovale and A. maculatum, as well as the description of morphohistological characters of the male reproductive system of ticks of the genus Amblyomma, in order to evaluate these characters within the current clustering proposals. In addition, 16S rDNA and COI (mitochondrial) molecular markers were used to study the genetic relationships of the species. The results show that the tick male reproductive system and its germ cells contain useful candidate characters for taxonomical analyses of Ixodida.
Keywords: Cryptic species; Histology; Molecular markers; Spermiotaxonomy; Ticks